Biotransformation of Toxic Metal Compounds by Fungi - Sutjaritvorakul, Thanawat (Journal of Advanced Development in Engineering and Science, 2023)
In nature, fungi are saprotrophic degraders of organic substances, and play an important role in biogeochemical cycle. Many fungi show distinguished ability to mobilize metals and metalloids from insoluble compounds such as metal phosphates, sulphides, carbonate, oxide and mineral ores by secretion of fungal metabolites (e.g. organic acid). They can also immobilize metal ion by extracellular precipitation as metal oxalate complexes. Metal transformation by insoluble metal oxalate formation is a process of marked environmental significance associated with fungal survival, bioremediation, mineral weathering and metal detoxification. Predicated on the ability of fungi in both mobilization and immobilization, it is plausible to exploit fungal ability to transform metals and metalloids for biotechnological application for metal recovery from smelter sludge, low grade ores, and other solid wastes.